Laboratory and Instrumental Characteristics of Chronic Hepatitis C - Shamsiyeva Muattar Axmatovna (Scientific Trends, 2025)
In terms of fibrosis and disease progression, the relationship between HCV and steatosis is unclear. HCV genotype 3 is clearly associated with steatosis. In some patients, steatosis may be associated with the development of fibrosis. The mechanisms underlying this association are unknown. This article describes and discusses the main and clinical-laboratory and instrumental aspects of the relationship between the development of steatosis and fibrosis and the response to treatment in patients with chronic hepatitis C.
Keywords: Chronic hepatitis C, hepatotropic virus, hepatocytes, fibrosis tissue.